The role of pharmacopoeia in the context of globalization of world economies and its development prospects - A. V. Titova; N. P. Sadchikova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article reviews the process of development and the role of national and regional pharmacopoeias in the context of globalization of world economies. Three major paths of globalization identified are: enlargement of national pharmacopoeias’ area of influence, formation of supranational (regional and supraregional) pharmacopoeias and harmonization of pharmacopoeias. The article draws a conclusion on interrelation of national and regional pharmacopoeias that aim to contribute to each other’s development. Harmonization of pharmacopoeias should follow the path of alignment of test methods and analytical procedures and at the same time accommodate national factors and priorities of countries that are involved in harmonization.